Lithostratigraphy and biostratigraphy of the upper cretaceous succession of Southeastern Sinai, Egypt - Medhat M.M. Mandur (Egyptian Journal of Petroleum)
The calcareous nannofossil of the Upper Cretaceous successions exposed at Taba and El sheikh Attia sections at Southeastern Sinai in Egypt have been studied to contribute in the understanding of lithostratigraphy and biostratigraphy. These sediments are subdivided into six rock units (from older to younger): Raha, Abu Qada, Wata, Matulla, Thelmet and Sudr. According to its calcareous nannofossil contents the succession is subdivided into 13 biozones and subzones. They are from the base to top Microrhabdulus decoratus (CC10), Quadrum gartneri (CC11), Lucianorhabdulus maleformis (CC12), Marthasterites furcatus (CC13), Micula decussata (CC14), Reinhardtites anthophorus (CC15), Aspidlithus parcus (CC18), Calculites ovalis (CC19), Ceratolithoides aculeus (CC20), Reinhardtites levis (CC24) Zones, and Subzones Arkhangelskiella cymbiformis (CC25a), Lithraphidites quadratus (CC25b) and Micula murus (CC25c). By means of calcareous nannofossil three stage boundaries are discussed they are: the Cenomanian/Turonian, the Santonian/Campanian and the Campanian/Maastrichtian.